Underexploited vegetables of Eastern and North-Eastern India: A treasure of nutritional compounds - Saha, Gourab; Pal, Saheb (Indian Horticulture, 2026)
Underutilized vegetable crops are those that are not widely cultivated compared to major vegetable crops. Many of these crops are region-specific, particularly in the Eastern and Northeastern states of India. The term “underutilized” is relative: a vegetable that is common in one area may be considered underutilized in another. Various parts of these vegetables are rich in essential minerals, vitamins, phytopigments, and antioxidants, which can help prevent lifestyle-related chronic diseases. Increasing awareness about the edible parts and nutritional properties of these vegetables can aid in their popularization and conservation, contributing to nutritional security and enhancing farm profitability through crop diversification.